Exploration of themes based twitter data in fraud-forensic accounting studies - A. A. G. S. Utama; Basuki Basuki (Cogent Business & Management, 2022)
The rapid development of information technology is also followed by developing databases and information based on social media. Social media Twitter is one area for disclosing accounting information in tweets, retweets, and other posts. This study aims to explore fraud-forensic accounting disclosures from the viewpoint of the four largest public accounting firms in the world (The Big 4) on the Twitter database. The approach used in this research is exploratory qualitative, with the content analysis method using NVivo software R1. The data collected a target of around 1000+~tweets. Researchers logged onto Twitter (as @agunggdeagung) and searched for all tweets containing the hashtag #fraud #forensic #accounting # big4. This research produces the theme of business, knowledge, time, and reports, and the themes of accounting, fraud, and forensics, which have already been defined as keywords in disclosure on social media Twitter. This research implies that in carrying out a qualitative approach with the twitter database, elements of the domain, community (user), information posts, and powerful data-based analysis software must be fulfilled.
Keywords: 650; exploration; content analysis; accounting; fraud; forensics; NVivo; themes